Comparing Review Strategies in the Classroom: Self-Testing Yields More Favorable Student Outcomes Relative to Question Generation. (April 2018) - Lloyd, E. Paige; Walker, Ryan J.; Metz, Molly A.; Diekman, Amanda B.
Although previous research has demonstrated that guided testing (i.e., self-testing) and question generation effectively increase retention compared to control methods, no work has simultaneously implemented both strategies in the classroom. In a semester-long study designed to maximize experimental control in a naturalistic setting, we adapted both review strategies for an introduction-level psychology course. We found that guided testing produced better student performance on exams than generating one's own practice questions. Additionally, students evaluated guided testing more positively than question generation. These findings build upon previous guided testing and question generation work by showing that, in the context of an introductory classroom, guided testing is more effective and efficient than generating questions.